Organ Preservation for Adenoid Cystic Carcinoma of the Larynx. (24th April 2013) - Misiukiewicz, Krzysztof J.; Camille, Nadia; Tishler, Roy; Haddad, Robert; Limaye, Sewanti; Posner, Marshall
Abstract : Objectives: Two cases of adenoid cystic carcinoma (ACC) of the larynx were treated with chemoradiotherapy (CRT) for organ preservation. We reviewed case series and current literature to contrast the potential role of primary CRT as an organ‐sparing modality with standard laryngectomy and radiotherapy in patients with laryngeal ACC. Methods: Two treatment‐naïve patients with laryngeal ACC treated at Dana‐Farber Cancer Institute between 2002 and 2007 were identified. Both patients were offered standard laryngectomy followed by adjuvant radiotherapy or organ‐sparing treatment modality. Results: Both patients were males, aged 57 and 73. The patients completed a course of combined chemoradiotherapy with weekly carboplatin and paclitaxel and 7–8 weeks of radiotherapy to a total dose of 6, 600 and 7, 000 cGy over 50 and 57 days, respectively. There were no treatment breaks or delays because of toxicity. The major toxicities reported by both patients, as anticipated, were Grade 3 mucositis, desquamative dermatitis, and severe dysphagia, all of which resolved. Both patients are alive with local regional control and functional larynx; one at 112+ months with pulmonary metastases at 54 months, and the other disease free at 60+ months. Conclusions: Definitive chemoradiation with weekly carboplatin and paclitaxel may be a potential alternative to the current standard of surgery and radiation for patients with locally advanced laryngeal ACC who request an organ‐sparing approach. In this group of patients, salvage laryngectomy may be reserved for those who are locally recurrent or chemoradiotherapy resistant. Although CRT provided long‐term local regional control in our two patients, there are evident limitations in obtaining evidence for a determination of treatment of rare diseases. This report provides support for following an organ preservation plan in selected patients. Abstract : Two cases of ACC of the larynx were treated with CRT for organ preservation. The patients completed a course of combined chemoradiotherapy with weekly carboplatin and paclitaxel and radiotherapy. Both patients are alive with local regional control and functional larynx, therefore, chemoradiation with weekly carboplatin and paclitaxel may be a potential alternative to the current treatment.